Compound-Specific Chlorine Isotope Analysis of Organochlorine Pesticides by Gas Chromatography-Negative Chemical Ionization Mass Spectrometry - Jing Zhang; Shenghua Liu; Jianye Gui; Xiaoya Li; Guochen Qi (Journal of Analytical Methods in Chemistry)
Compound-specific stable chlorine isotope analysis (CSIA-Cl) is an important method for identifying sources of organochlorine contaminants and helping assess their quantification of transformation processes. However, the present CSIA-Cl is challenged by either redundant conversion pretreatment or complicated mathematical correction. To overcome the mentioned problems, a novel method has been developed for the CSIA-Cl of eight organochlorine pesticides using gas chromatography-negative chemical ionization mass spectrometry (GC-NCI-qMS) in this study. The instrument parameters, acquisition mode, and required injection amounts were optimized in terms of the precision of GC-NCI-qMS. An ionization energy of 90 eV and emission current of 90 μA were selected, and the precisions for eight organochlorine pesticides were in the range of 0.37‰–2.15‰ in single ion monitoring (SIM) mode when the injected amount was 0.50 mg L−1 (viz. 0.5 ng on column). Furthermore, when standards from Supelco and O2si were calibrated using standards from AccuStandard regarded as external isotope standard, chlorine isotope composition of α-hexachlorocyclohexane (α-HCH) and 2, 2-dichloro−1, 1-bis (4-chlorophenyl) ethylene (p, p′-DDE) in Supelco and O2si was confidently differentiated. The provenance identification method was validated by three organochlorine contaminated groundwater samples and showed a prospect in identifying the source of organochlorine pesticides.